Doing things differently: Rethinking monitoring and evaluation to understand change - and Saferworld (Saferworld, 2016)
Doing things differently: Rethinking monitoring and evaluation to understand change Learning paper Over the past four years, Saferworld has put in place a way of monitoring, evaluating and learning from our work focused on behaviour and relationship change. This paper outlines the process we have gone through to adapt, embed, and embrace an approach inspired by Outcome Mapping and Outcome Harvesting (OH). Key benefits of our monitoring, evaluation and learning approach are: It is simple, but promotes complex discussion and analysis. It allows conflict- and gender-sensitivity to be built into programmes; it promotes analysis of and adaptation to context. Bringing front-line staff and partners into wider conversations with others substantially increases cross-organisational learning.